Penerapan Strategi Three-Stage Fishbowl Decision untuk Meningkatkan Pemahaman Konsep dan Aktivitas Belajar Siswa - Sri Lestari Handayani; Sarwi Sarwi; Putut Marwoto (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2016)
The purpose of this research were to improve the student activities and conceptual understanding using three-stage fishbowl decision strategy in pressure subject. This research design was the pretest-posttest control group design. The sample of this research was 65 students of 8th grade that was determined by using purposive sample method. The data were collected by test, observation, and documentation. The data was analyzed by using gain test and one-tail t-test. The gain-test was obtained that the activity and students understanding of pressure concept for experimental group was increased in medium level, whereas for control group in minimum level. The one-tail t-test was obtained that the activity and students understanding of pressure concept for the experimental group were better than the control group.